What Makes Village Economic Development Successful? Evidence in Two Villages, Malang Regency Indonesia - La Ode Machdani Afala; Restu Karlina Rahayu (Universitas Sultan Ageng Tirtayasa, 2023)
Studies of villages in several countries show an increasing trend regarding the success of village economic development. However, developing the rural economy in a developing country like Indonesia needs more insight into its investigations. This article discusses the success factors for economic development at the village level, especially in Indonesia's new era of village development. This study used a qualitative method by interviewing several informants, observing, and collecting secondary data in two villages, Sanankerto and Pujon Kidul, Malang Regency. We found that village transformation in recent years has strengthened villages independence in managing their economies and contributing to the welfare of village communities. The existence of Village Economic Enterprise (BUMDes), in this case, acts as the main driving force that plays a role in the development of the village economy. Some factors contributed to the transformation of the village and the success of the village's economic development, namely strong entrepreneurial leadership, institutional reform, inclusiveness, and community participation. This study has significantly contributed to improving economic governance at the village level.